1987
DOI: 10.1021/bi00392a004
|View full text |Cite
|
Sign up to set email alerts
|

Binding of the DNA polymerase .alpha.-DNA primase complex to the nuclear matrix in HeLa cells

Abstract: It is well-known that there are multiple forms of DNA polymerase alpha. In order to determine which form(s) is (are) tightly bound, the activities were dissociated from DNA-poor nuclear matrices, with octyl beta-D-glucoside. Sucrose gradient sedimentation analysis revealed three bands with s values of 7.5, 10.5, and 13. The 7.5S form was free of DNA primase and represented only 10% of the total DNA polymerase alpha bound to the nuclear matrix. The 13S and the 10.5S forms each contained DNA primase activity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 44 publications
(79 reference statements)
2
17
0
Order By: Relevance
“…As shown in Table V, soluble DNA pol ␣ activity remained stable up to 6 h after serum dilution and changed relatively little, being doubled after 30 h, in agreement with previous data [Foster and Collins, 1985;Fry and Loeb, 1986;Vishwanatra et al, 1986;Collins and Chu, 1987;Wang, 1991], and conceivably representing the effect of de novo synthesis of the enzyme [Miyazawa et al, 1993]. Nuclear DNA pol ␣ activity started to rise at 6 h after dilution and then gradually increased, reaching a plateau value at 22 h. Overall, this activity showed a fourfold increase at 30 h. A striking increase in nuclear matrix-bound DNA pol ␣ activity was seen as early as 2 h after dilution.…”
Section: Dna Pol ␣ and Dna Primase Activities In Subcellular Fractionsupporting
confidence: 91%
“…As shown in Table V, soluble DNA pol ␣ activity remained stable up to 6 h after serum dilution and changed relatively little, being doubled after 30 h, in agreement with previous data [Foster and Collins, 1985;Fry and Loeb, 1986;Vishwanatra et al, 1986;Collins and Chu, 1987;Wang, 1991], and conceivably representing the effect of de novo synthesis of the enzyme [Miyazawa et al, 1993]. Nuclear DNA pol ␣ activity started to rise at 6 h after dilution and then gradually increased, reaching a plateau value at 22 h. Overall, this activity showed a fourfold increase at 30 h. A striking increase in nuclear matrix-bound DNA pol ␣ activity was seen as early as 2 h after dilution.…”
Section: Dna Pol ␣ and Dna Primase Activities In Subcellular Fractionsupporting
confidence: 91%
“…Numerous studies have suggested that there must be an organizing structure such as the nuclear matrix that helps coordinate spatial regulation of DNA synthesis (Dijkwel et al 1979;Berezney and Buchholtz 1981;Hunt and Vogelstein 1981;Carri et al 1986;Collins and Chu 1987;Vaughn et al 1990;Neri et al 1992;Hozak et al 1993). Components of the nuclear substructure that have been implicated in establishing the pattern of DNA replication sites are the nuclear lamins.…”
mentioning
confidence: 99%
“…Hence, the amount of bound pol a was essentially constant through S phase, suggesting a fairly constant rate of DNA replication through S phase. This finding is not in agreement with a local minimum of bound pol a in mid-S phase (8,12) and not consistent with a local minimum in the DNA replication rate in mid-S phase (7,12). Assuming that the pol a molecules replicate the lagging strand and an equal number of pol 8 molecules replicate the leading strand (10,32,33), we calculated a chain elongation (9) 0.94 ± 0.06 1.07 ± 0.07 0.99 ± 0.08 a Relative to the average for S-phase nuclei.…”
mentioning
confidence: 87%
“…On the other hand, after paraformaldehyde fixation, pol a is localized to the nucleus of all interphase cells in exponentially growing cultures (1,18). Other studies indicate that a fraction of pol a is bound to the nuclear matrix (8,9,12,27,28,36,44); the association seems to be S-phase specific (8,12,27). In this study, we have used flow cytometry and confocal laser scanning microscopy to determine the expression, nuclear binding, and localization of pol a in resting and proliferating cells.…”
mentioning
confidence: 99%